(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article discusses the essence of the reforms being implemented in the field of music culture education in our country, the improvement of music education in general education schools, the pedagogical conditions for organizing modern lessons, the requirements for music culture teachers, their professional competencies, methods, techniques, tools, the main tasks of music lessons in schools, and the views of Eastern thinkers on the role and significance of music in personal development.